Overcoming challenges to develop technology for child health. (18th August 2022) - Mills, Nathaniel; Howsley, Philippa; Bartlett, Clare M; Olubajo, Linda; Dimitri, Paul
Abstract: Millions of children and young people (CYP) in the UK are affected by chronic or rare health conditions. Rapid advances in science and technology have resulted in CYP with chronic and rare conditions now surviving well into adulthood. New technologies have the potential to improve short- and long-term health outcomes for CYP with health conditions, prevent adult onset disease and complications, and reduce the burden on health services. There is thus a need for targeted investment and appropriate governance in child health technology development to address the specific needs of this population; health technology must be versatile to meet the social, anatomical, cognitive, psychological, and physiological changes inherent to childhood development. Despite the growing demand for health technology for a sizeable global population, industry still wrongly perceives the market size is relatively small, and health technology development is often localised and fragmented with limited scope for spread and adoption. These challenges can be overcome by validating and prioritising unmet needs, involving CYP and their families throughout the innovation pathway, facilitating effective partnerships with key stakeholders, and utilising national and international infrastructure and networks. This paper outlines five innovations supported by NIHR Children and Young People MedTech Co-operative that illustrate how common challenges in child health technology development can be overcome. It is essential that we continue to address such challenges and invest in the health and wellbeing of CYP.